Peran Tokoh Adat Osing dalam Pemanfaatan dan Penggunaan Tanah Ulayat. (Studi Empiris Di Desa Kemiren, Kecamatan Glagah, Kabupaten Banyuwangi) - Restu Adi Putra; Irham Rahman (UNES Law Review, 2023)
Customary land is a very important part of customary law communities so that its existence needs to be maintained and preserved. One form of the existence of customary land or customary land that is interesting to study more deeply is customary land in the Osing Kemiren traditional village, Glagah District, Banyuwangi Regency. Customary land or customary land for the Osing Kemiren customary law community is interpreted as an ancestral heritage that needs to be preserved so that in utilisation and use it is necessary to pay attention to the values of local wisdom that have been carried out for generations. The role of traditional leaders in the Osing Kemiren customary law community is very important to preserve customary land or customary land in terms of the utilisation and use of the land. The research method used in this research is to use the sociological juridical method, namely going directly to the community. So that the results obtained that based on the results of research conducted in the field, Customary Land or Customary Land according to the Osing Kemiren village customary law community is interpreted as individual land which in its use and utilisation still upholds local wisdom values in this case still using customs that apply from generation to generation. Customary figures in the Osing Kemiren customary law community have a role to provide advice and input in every activity related to land in the region.